2008
DOI: 10.1160/th08-04-0242
|View full text |Cite
|
Sign up to set email alerts
|

Altered bioavailability of platelet-derived factor VIII during thrombocytosis reverses phenotypic efficacy in haemophilic mice

Abstract: Ectopic delivery of factor VIII (FVIII) to megakaryocytes (Mk) represents a viable approach for localized tenase generation by concentrating the FVIIIa/FIXa enzyme-cofactor complex onto activated platelet membranes. We utilized a core rat platelet factor 4 (PF4) promoter for Mk/platelet-restricted expression of human B-domain-deleted (hBDD) FVIII within the background of a haemophilia A mouse (rPF4/hBDD/FVIII-/-). Platelets from rPF4/hBDD/FVIII(-/-) mice contained approximately 122 mU FVIII:C/1 x 10(9) platele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…Previous studies by our group 10,11,16,17 and others [20][21][22][23] using mouse models have demonstrated that platelet-targeted expression of FVIII may be a promising approach for gene therapy of hemophilia A and hemophilia A with inhibitors. In this study, we established a novel immunocompromised hemophilia A mouse model and used humanized mouse models to explore the feasibility and efficacy of targeting FVIII expression to human platelets for hemophilia A gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by our group 10,11,16,17 and others [20][21][22][23] using mouse models have demonstrated that platelet-targeted expression of FVIII may be a promising approach for gene therapy of hemophilia A and hemophilia A with inhibitors. In this study, we established a novel immunocompromised hemophilia A mouse model and used humanized mouse models to explore the feasibility and efficacy of targeting FVIII expression to human platelets for hemophilia A gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Rep 78 immunodetection was established in 293 cells transfected with FLAG-tagged Rep plasmids (pFLAG/wtRep, pFLAG/dRep, or pFLAG/sRep), and at 48 h, protein-solubilized lysates were prepared for 4% to 15% SDS/PAGE and immunoblotting as previously described (14). Immunodetection was performed by enhanced chemiluminescence by using anti-FLAG M2 (1:1,000; Sigma) and anti-GAPDH MAB374 (1:1,000; Millipore) as a loading control.…”
Section: Methodsmentioning
confidence: 99%
“…Although the AAV integrating elements (i.e., TRs or p5IEE) are readily incorporated into herpesvirus (12,13) or Ad vectors (14)(15)(16), Rep 78/68 is poorly tolerated. Moderate success has been achieved with the use of complex homologous recombination strategies (17) and helper-dependent (18) or tightly regulated (19) expression systems, although the latter two approaches are additionally restricted by the helper-dependent nature of Rep 78-containing Ad.…”
mentioning
confidence: 99%
“…The other is that they are less likely to activate the host-cell defense machinery than constitutive viral promoters and therefore, the development of immune response to transgene product may be reduced or circumvented [43]. The promoters that have been employed to direct megakaryocyte/platelet lineage-specific transgene expression include those that control the expression of genes encoding GPIIb (αIIb) [44-54], GPIbα [55-57], GPVI [57], platelet factor 4 (PF4) [58-60], and c-mpl [61,62]. All of these promoters are activate in both megakaryocytes and platelets.…”
Section: Platelet Manipulation For Disease Treatmentmentioning
confidence: 99%
“…The studies demonstrated that ectopic expression of FVIII in platelets under control of the PF4 promoter had no effect on α-granule-derived platelet factor V/Va function. The amount of FVIII per platelet was decreased, with a parallel decrease in efficacy when transgenic mice were infused with thrombopoietin [60]. …”
Section: Ectopic Expression Of Coagulation Factors In Megakaryocytmentioning
confidence: 99%